Costs optimization in anaesthesia - Martelli, Alessandra (Acta Biomedica Atenei Parmensis, 2015)
Objectives: The aim of this study is to analyze the direct cost of different anaesthetic techniques used within the Author’s hospital setting and compare with costs reported in the literature. Methods: Mean cost of drugs and devices used in our local Department of Anaesthesia was considered in the present study. All drugs were supplied by the in-house Pharmacy Service of Parma’s General Hospital. All calculation have been made using an hypothetical ASA1 patient weighting 70 kg. The quality of consumption and cost of inhalation anaesthesia with sevoflurane or desflurane at different fresh gas flow were analyzed, and the cost of total venous anaesthesia (TIVA) using propofol and remifentanil with balanced anaesthesia were also analyzed. In addition, direct costs of general, spinal and sciatic-femoral nerve block anaesthesia used for common plastic surgery procedures were assessed. Result: The results of our study show that the cost of inhalational anaesthesia decreases using fresh gas flow below 1L, and the use of desflurane is more expensive. In our Hospital, the cost of TIVA is more or less equivalent to the costs of balanced anaesthesia with sevoflurane in surgical procedure lasting more than five hours. The direct cost was lower for the spinal anaesthesia compared with general anaesthesia and sciatic- femoral nerve block for some surgical procedures. (www.actabiomedica.it)